Adsorption of Cr(VI) by iron oxide functionalized polyethyleneimine (PEI) coated activated carbon-silica composites - Qhubu, Mpho Cynthia (Vaal University of Technology, 2020)
Water scarcity due to limited resources and pollution of the little available water by organic and inorganic contaminants remains as one of the critical issues of the 21st century. Several treatment methods have been developed, with some being used successfully at industrial scale but many challenges including secondary sludge generation, high operation costs, high maintenance costs and high energy input were observed. In this study, the adsorption process was explored as an effective means for the removal of Cr(VI) ions from aqueous solution due to its economic feasibility and use of abundantly available adsorbents. Amongst the many available adsorbents, this work focused on exploring functionalized activated carbons (ACs) as adsorbents for Cr(VI) ions due to their favorable adsorption characteristics which involve large surface area, high porosity, and high radiant stability. The iron oxide functionalized polyethyleneimine activated carbon-silica composites were prepared through co-precipitation of Fe(II) and Fe(III) over Macadamia activated carbon to form the AC-Fe3O4 co-shell which was reacted with tetraethylorthosilicate (TEOS) and the polyethyleneimine (PEI). The different adsorbents prepared were labelled AC-Fe3O4, AC-Fe3O4-SiO2 and AC-Fe3O4-SiO2-PEI. The adsorbents were further characterized using elemental analysis (CHNS), thermo gravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Fourier transform infrared (FTIR) spectroscopy, Brunauer-Emmett-Teller (BET), transmission electron spectroscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). FTIR displayed successful attachment of Fe3O4 and SiO2 with bands at 404 and 786 cm-1 being assigned to the asymmetric vibration of Fe-O and Si-O-Si while the asymmetric stretch of Si-OH is observed at 1066 cm-1. XRD showed the presence of magnetite particles in the adsorbents confirmed by the JCPDS 00-019-0629. EDS revealed the presence of Fe, Si, and N atoms which can relate to successful incorporation of the desired functional groups. Each of these materials were evaluated for their Cr(VI) ion removal through batch adsorption experiments where one parameter at a time was varied while all others were fixed. The parameters investigated included the effect of pH, contact time, initials Cr(VI) concentration, adsorbent dosage concentration and temperature. The optimum conditions were obtained at pH 3, initial concentration 2.5 mg/L, contact time of 120 min for AC-Fe3O4-SiO2-PEI. The optimization of each parameter was done in order to determine the conditions in which the adsorbents work best in the uptake of Cr(VI). All the three studied adsorbents showed acceptable adsorption performance for the removal of Cr(VI) from aqueous solutions. Adsorption isotherms studied confirmed that the adsorption data in all the three adsorbents fitted well into the Langmuir isotherm, demonstrating a homogeneous monolayer coverage. Regarding the kinetic studies, the adsorption data were best described by the pseudo-second order rate model with R2 values of 0.974, 0.974 and 0.962 for AC-Fe3O4, AC-Fe3O4-SiO2 and AC-Fe3O4-SiO2-PEI, respectively. The adsorption capacity observed from the present study (6.62, 3.92 and 5.48 for AC-Fe3O4, AC-Fe3O4-SiO2 and AC-Fe3O4-SiO2-PEI, respectively) were satisfactory and suitable as compared to those reported in literature. Thermodynamics data of the adsorption processes revealed a feasible spontaneous endothermic adsorption process which also confirmed that the reaction process occurred through chemisorption.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Adsorption; Iron oxide; Polyethyleneimine (PEI); Carbon-silica composites; Organic compounds; Inorganic compounds; Cr(VI); Dissertations, Academic -- South Africa.; Adsorption.; Water -- Pollution.; Water -- Purification.; Chemisorption.